Downscaling and its Limitations on Climate Change Impact Assessments - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Presentation by Sepo Hachigonta from University of Cape Town. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya.